The moderated-mediation model of Emotional Intelligence and Negative Affect in the aggressive behavior within the General Aggression Model (GAM) - Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Megías-Robles, Alberto; Cabello-González, Rosario; Fernández-Berrocal, Pablo (My University, 2018)
Aggressive behaviour has been the focus of numerous investigations given its prevalence and undesirable consequences for aggressors and victims. The General Aggression Model (GAM) offers an integrative explanation of this behaviour based on three stages: (1) inputs (personal and situational factors); (2) routes or the individual internal state (affects, cognitions and arousal), and (3) outcomes: appraisal and decision processes with a final (non) aggressive result. Looking for protective factors within the model in order to diminish aggression is being the current focus of researchers. Previous literature has pay attention to two relevant variables: emotional intelligence (EI) and negative affect (NA). Specifically, the perceiving and managing branches of EI seem to play a protective role in the aggressive behaviour, while NA appear as a risky factor. The aim of the present study is to analyse the role of these three variables (perceiving EI, managing EI and NA) within the stages of the GAM model. We hypothesized to find a conditional indirect effect of the perceiving branch of EI on aggression total scores through NA as a function of the managing branch of EI (the moderated mediation model). 395 students from the University of Málaga (Spain) took part in the experiment. Participants were assessed in ability EI, NA, and aggression levels throughout the questionnaires MSCEIT, PANAS, and BPAQ. We conducted a moderate mediation analysis to explore our hypothesis. The results revealed a significant negative indirect effect of MSCEIT perceiving on BPAQ total mediated through PANAS NA. Therefore, a adequate emotional perception is useful in the reduction of the aggression level via the indirect effect of NA.Therefore, a adequate emotional perception is useful in the reduction of the aggression level via the indirect effect of NA. In addition, MSCEIT managing moderates the impact of negative affect on aggression.
Keywords: Inteligencia emocional; Agresividad; Emotional Intelligence; Negative Affect